Acoustic stress responses in juvenile sea bass Dicentrarchus labrax induced by offshore pile driving. (January 2016) - Debusschere, Elisabeth; Hostens, Kris; Adriaens, Dominique; Ampe, Bart; Botteldooren, Dick; De Boeck, Gudrun; De Muynck, Amelie; Sinha, Amit Kumar; Vandendriessche, Sofie; Van Hoorebeke, Luc; Vincx, Magda; Degraer, Steven
Abstract: Underwater sound generated by pile driving during construction of offshore wind farms is a major concern in many countries. This paper reports on the acoustic stress responses in young European sea bass Dicentrarchus labrax (68 and 115 days old), based on four in situ experiments as close as 45 m from a pile driving activity. As a primary stress response, whole-body cortisol seemed to be too sensitive to 'handling' bias. On the other hand, measured secondary stress responses to pile driving showed significant reductions in oxygen consumption rate and low whole-body lactate concentrations. Furthermore, repeated exposure to impulsive sound significantly affected both primary and secondary stress responses. Under laboratory conditions, no tertiary stress responses (no changes in specific growth rate or Fulton's condition factor) were noted in young sea bass 30 days after the treatment. Still, the demonstrated acute stress responses and potentially repeated exposure to impulsive sound in the field will inevitably lead to less fit fish in the wild. Highlights: Pile driving is perceived as an acoustic stressor by juvenile fish. In situ experiments as close as 45 m from a pile driving activity were performed. Strong secondary stress response was observed in juvenile sea bass during exposure. Under optimal lab conditions, no long term reduction in fitness was noted. Abstract : Capsule abstract: Exposure to offshore pile driving induced strong secondary responses in juvenile European sea bass, resulting in a temporary reduction of fitness.